Optimization of Pd Membrane Reactor for Direct Oxidation of Aromatic Compounds - Milad Rasouli; Sahar Chitsazan; Mohammad Hossein Sayyar; Nakisa Yaghobi; Babak Bozorgi (ASEAN Journal of Chemical Engineering, 2011)
Computational fluid dynamic has already become a widely used and indispensable design and optimization tool in many technical areas. In the present work, the CFD simulations have been coupled with complex chemical reactions to model a membrane tubular reactor which is used to produce phenol from benzene in the vapor phase. Hydrogen dissociates on the palladium layer and reacts with oxygen to give active oxygen species, which attack benzene to produce phenol. In principal, reaction occurs in the surface of palladium and conversion of benzene is increased by changing the length and diameter of the Pd coated PSS tubes. The reactor length and diameter are two geometrical factors which are concerned in the present study. Although increasing the reactor length increase the conversion of benzene to phenol but the concentration of the phenol start to decrease. Based on the data provided by the experiments, a mathematical model has been constructed to conduct a simulation which leads us to an optimum design of a new tubular membrane micro-reactor.